Improving patient care: the implementation of change in health care - Grol, Richard; Wensing, Michel; Eccles, Martin; Davis, David (Wiley, 2013)
As innovations are constantly being developed within health care, it can be difficult both to select appropriate new practices and technologies and to successfully adopt them within complex organizations. It is necessary to understand the consequences of introducing change, how to best implement new procedures and techniques, how to evaluate success and to improve the quality of patient care. This comprehensive guide allows you to do just that. Improving Patient Care, 2nd edition provides a structure for professionals and change agents to implement better practices in health c
Description based upon print version of record
Keywords: Electronic books; Verbesserung; Krankenpflege